Binding of Plasminogen to Streptococcus suis Protein Endopeptidase O Facilitates Evasion of Innate Immunity in Streptococcus suis - Zhou, Yang; Yan, Kang; Sun, Chengfeng; Liu, Feng; Peng, Wei; Chen, Huanchun; Yuan, Fangyan; Bei, Weicheng; Li, Jinquan (Frontiers in Microbiology, 2021)
The Gram-positive bacterial species Streptococcus suis is an important porcine and human pathogen that causes severe life-threatening diseases associated with high mortality rates. However, the mechanisms by which S. suis evades host innate immunity remain elusive, so identifying novel virulence factors involved in immune evasion is crucial to gain control over this threatening pathogen. Our previous work has shown that S. suis protein endopeptidase O (SsPepO) is a novel fibronectin-binding protein. Here, we identified that recombinant SsPepO binds human plasminogen in a dose-dependent manner. Moreover, the binding of SsPepO and plasminogen, upon the activation of urokinase-type plasminogen activator, generated plasmin, which could cleave complement C3b, thus playing an important role in complement control. Additionally, a SspepO-deficient mutant showed impaired adherence to plasminogen as well as impaired adherence to and invasion of rat brain microvascular endothelial cells compared with the wildtype strain. We further found that the SspepO-deficient mutant was efficiently killed by human serum and blood. We also confirmed that the SspepO-deficient mutant had a lower mortality rate than the wildtype strain in a mouse model. In conclusion, these results indicate that SsPepO is a novel plasminogen-binding protein that contributes to S. suis immune evasion.